2020
DOI: 10.1192/j.eurpsy.2020.83
|View full text |Cite
|
Sign up to set email alerts
|

The effect of sex on suicide risk during and after psychiatric inpatient care in 12 countries—An ecological study

Abstract: Background. Suicide risk in patients is markedly elevated during psychiatric inpatient care, as well as after discharge. However, it is unclear whether, and to what extent, this increased suicide risk varies between sex. Thus, the aim of this study was to analyze sex differences for suicides during and after psychiatric hospitalization in various countries. Methods. National suicide mortality rates and inpatient-related suicide rates (three intervals: during psychiatric inpatient treatment, 1 month, and 1 year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 26 publications
2
1
0
Order By: Relevance
“…Adjustment disorders are not frequently included in epidemiological mental health studies, and further research is needed to determine their exact role with regard to suicide risk. Second, although postdischarge suicide rates in this study were higher among males compared with females (1.3% vs 0.9%), consistent with an earlier study, females had disproportionately high suicide rates compared with the general population (SMR, 47.6), in line with previous evidence and potentially explained by higher treatment-seeking rates among females with severe disorders . In line with a study among Danish patients, we found that admission for bipolar disorder was associated with postdischarge suicide among females.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Adjustment disorders are not frequently included in epidemiological mental health studies, and further research is needed to determine their exact role with regard to suicide risk. Second, although postdischarge suicide rates in this study were higher among males compared with females (1.3% vs 0.9%), consistent with an earlier study, females had disproportionately high suicide rates compared with the general population (SMR, 47.6), in line with previous evidence and potentially explained by higher treatment-seeking rates among females with severe disorders . In line with a study among Danish patients, we found that admission for bipolar disorder was associated with postdischarge suicide among females.…”
Section: Discussionsupporting
confidence: 92%
“…Adjustment disorders are not frequently included in epidemiological mental health studies, and further research is needed to determine their exact role with regard to suicide risk. Second, although postdischarge suicide rates in this study were higher among males compared with females (1.3% vs 0.9%), consistent with an earlier study, 29 females had disproportionately high suicide rates compared with the general population (SMR, 47.6), in line with previous evidence 30 and potentially explained by higher treatment-seeking rates among females with severe disorders. 31 In line with a study among Danish patients, 32 we found that admission for bipolar disorder was associated with postdischarge suicide among females.…”
Section: Discussionsupporting
confidence: 91%
“…Such findings may be relevant compared to a study investigating gender inequalities in inpatient suicide rates during psychiatric inpatient treatment and after discharge in 12 countries. The authors reported a similar gender gap in suicide risk, with females having higher suicide rates during and after hospitalization [ 40 ]. However, contrasting results have been reported, with a higher risk in male patients [ 41 ].…”
Section: Discussionmentioning
confidence: 99%